On Sufficient Conditions for Absolute Convergence of Double Fourier Series of Almost-Periodic Bezikovich Functions (London Journal of Research In Science: Natural and Formal, 2024)
The paper investigates sufficient conditions for the absolute convergence of trigonometric Fourier series of almost-periodic functions in the sense of Bezikovich in the case when the Fourier exponents have a single limiting point at infinity. A higher-order continuity module is used as a structural characteristic of the function under consideration.